Patient Power: A feasibility study on the impact of providing a bedside notepad to encourage patients to ask questions following surgery - Breanna Wright; Justin Aylward; Sharon Allsop; Alyse Lennox; Nicholas Faulkner; Peter Bragge (Elsevier, 2024)
Objective: This study aimed to evaluate a behaviour change strategy to enhance the patient voice in the early post-operative setting. Methods: The Patient Power notepad was evaluated in an uncontrolled, single-group, mixed-methods trial including a patient evaluation survey and staff phone interviews. Results: Patients thought that the notepad was well-designed and prompted them to think of and ask questions. They strongly agreed that healthcare practitioners answered health-related questions fully and carefully. Staff reported that the notepad not only provided an easy mechanism through which patients and their families could communicate with their healthcare team, but it also created a permissive environment where questions were encouraged. Conclusion: The Patient Power notepad provided an easy, acceptable and scalable intervention to encourage patients to engage more in their healthcare and specifically to ask questions about their care. By providing a structured tool for capturing patient concerns, symptoms, and questions, this innovation holds the potential to enhance patient satisfaction, treatment adherence, and overall healthcare outcomes. Innovation: By facilitating comprehensive information exchange and the potential to promote shared decision-making, this innovation has the potential to improve patient satisfaction, treatment adherence, and overall healthcare outcomes.